2010
DOI: 10.1055/s-0030-1249938
|View full text |Cite
|
Sign up to set email alerts
|

Glucosylation of Steroidal Saponins by Cyclodextrin Glucanotransferase

Abstract: It is known that the sugar chains of steroidal saponins play an important role in the biological and pharmacological activities. In order to synthesize steroidal saponins with novel sugar chains in one step for further studies on pharmacological activity, we here describe the glucosylation of steroidal saponins, and 5 compounds, timosaponin AIII (1), saponin Ta (2), saponin Tb (3), trillin (4) and cantalasaponin I (5), were converted into their glucosylated products by Toruzyme 3.0 L, a cyclodextrin glucanotra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 22 publications
(28 reference statements)
0
13
0
Order By: Relevance
“…Rhizoma Anemarrhenae (Zhimu in Chinese), a wellknown traditional Chinese medicinal herb, which is officially listed in the Chinese Pharmacopoeia, has been effectively used for febrile diseases in oriental clinical practices. Timosaponin A-III (TAIII), a steroidal saponin isolated from the rhizomes of Anemarrhena asphodeloides (AA), has been credited with a wide spectrum of bioactivities, including improving learning and memory (16), inhibiting inflammation (17), suppressing allergic reaction (18), controlling hyperglycemic (19,20), activating autophagy (21) and inducing cancer cells apoptosis (22)(23)(24). However, the ability of TAIII to reverse MDR has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Rhizoma Anemarrhenae (Zhimu in Chinese), a wellknown traditional Chinese medicinal herb, which is officially listed in the Chinese Pharmacopoeia, has been effectively used for febrile diseases in oriental clinical practices. Timosaponin A-III (TAIII), a steroidal saponin isolated from the rhizomes of Anemarrhena asphodeloides (AA), has been credited with a wide spectrum of bioactivities, including improving learning and memory (16), inhibiting inflammation (17), suppressing allergic reaction (18), controlling hyperglycemic (19,20), activating autophagy (21) and inducing cancer cells apoptosis (22)(23)(24). However, the ability of TAIII to reverse MDR has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al also developed an enzyme associated five-step preparation method to produce high yield and purity Timo AIII from A. asphodeloides Bunge, which allowed us obtain efficient amount of Timo AIII for further study and product development (Lu et al, 2016). Although Timo AIII and Timo BII are mainly metabolized to sarsasapogenin in vivo, the sugar chain plays important roles in their pharmacological activities (Sy et al, 2008;Lee et al, 2010;Wang et al, 2010). The sugar chain in Timo AIII is indispensable to its pharmacological activities, and conversion of Timo BII to Timo AIII enhanced its cytotoxicity (King et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…So, Timo AIII presented most potential anti-cancer activity due to its specific sugar chain binding site. However, the hydrophobicity and low bioavailability of Timo AIII limited its efficacy in vivo, and many studies also focused on derivatization or drug delivery system design based on Timo AIII (Wang et al, 2010;Hu et al, 2011;Kim et al, 2014;Lu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A number of reports have suggested that transglycosylation by enzymes can be used to improve physiochemical functions such as taste, solubility in water, and oxidative stability of numerous active substances [15,16]. Among these enzymes, cyclodextrin glycosyltransferase (CGTase, 1,4-α- D -glucan: 1,4-α- D -glycopyranosyltransferase, cyclizing, EC 2.4.1.19) [17] has been reported to accelerate reactions between natural products and starch hydrolysate or β-cyclodextrin to produce glucosylated modifications of natural compounds such as hesperidin, glycosylglycerol [14,16] rutin [18], and steroidal saponins [19].…”
Section: Introductionmentioning
confidence: 99%